2015
DOI: 10.1021/am508939s
|View full text |Cite
|
Sign up to set email alerts
|

Self-Lubricity of WSex Nanocomposite Coatings

Abstract: Transition metal chalcogenides with lamellar structure are known for their use in tribological applications although limited to vacuum due to their easy degradation in presence of oxygen and/or moisture. Here we present a tailored WSe x coating with low friction (0.07) and low wear rates (3×10 -7 mm 3 Nm -1 ) even in ambient air. To understand the low friction behaviour and lower chemical reactivity a tribological study is carried out in a high vacuum tribometer under variable pressures (atmospheric pressure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Making composites with PTFE [118] and WC [119] were also claimed to improve the tribological properties of the coating. Meanwhile, it was also reported that if the crystalline order of the coating is increased, the humid resistance could be improved [120][121][122]. This phenomenon is also suggestive that the edge sites play an important role in the humidity dependence.…”
Section: Transition Metal Dichalcogenides (Tmds)mentioning
confidence: 88%
“…Making composites with PTFE [118] and WC [119] were also claimed to improve the tribological properties of the coating. Meanwhile, it was also reported that if the crystalline order of the coating is increased, the humid resistance could be improved [120][121][122]. This phenomenon is also suggestive that the edge sites play an important role in the humidity dependence.…”
Section: Transition Metal Dichalcogenides (Tmds)mentioning
confidence: 88%
“…1−4 Low friction stems from the ability to form an oriented film on the sliding surface, with the basal planes aligned parallel to the surface, due to low adhesion and shear strength between the planes. 5 At the nanoscale, a rotational disorder is expected between the planes in order to decrease dissipated energy and thus friction (incommensurate sliding). 4 One of the main drawbacks of pure TMD coatings (typically prepared by magnetron sputtering) is their low load-bearing capacity and limited wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Domínguez-Meister et al [22] have obtained the low friction coatings containing a composition of TMD nanocrystals with metal-based amorphous phase. This nanocomposition of the coatings allowed implementing low friction (0.07) and low wearing rate (3 10 -7 mm 3 N -1 m -1 ) even in ambient air.…”
Section: Tribological Properties Of the Mosex/nc-mo Coatingsmentioning
confidence: 99%